Ergebnisse der zoologischen Forschungen Dr. Z. Kaszab in der Mongolei. 150. Beitrag. Lepidoptera: Epermeniidae. - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The Epermeniidae collected by the expeditions to Mongolia of Dr. Z. Kaszab total two species. There is described an abberation of Epermenia ochreomaculella (Milliere).